2004
DOI: 10.1056/nejmoa031197
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Smad3 in Acute T-Cell Lymphoblastic Leukemia

Abstract: Loss of Smad3 protein is a specific feature of pediatric T-cell ALL. A reduction in Smad3 expression and the loss of p27Kip1 work synergistically to promote T-cell leukemogenesis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
102
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(108 citation statements)
references
References 11 publications
2
102
0
4
Order By: Relevance
“…56 Although there have been no mutations reported thus far in the Smad3 gene isolated from tumors, recent studies have provided direct evidence that Smad3 is an important tumor suppressor in pediatric T-cell acute lymphoblastic leukemia (ALL) and gastric cancer. 57,58 Whereas Smad3 mRNA is present at normal levels, Smad3 protein is absent in leukemic cells from children with T cell ALL. 57 Loss of Smad3 protein is a specific feature of pediatric T-cell ALL, but not pre-B-cell ALL.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…56 Although there have been no mutations reported thus far in the Smad3 gene isolated from tumors, recent studies have provided direct evidence that Smad3 is an important tumor suppressor in pediatric T-cell acute lymphoblastic leukemia (ALL) and gastric cancer. 57,58 Whereas Smad3 mRNA is present at normal levels, Smad3 protein is absent in leukemic cells from children with T cell ALL. 57 Loss of Smad3 protein is a specific feature of pediatric T-cell ALL, but not pre-B-cell ALL.…”
mentioning
confidence: 99%
“…57,58 Whereas Smad3 mRNA is present at normal levels, Smad3 protein is absent in leukemic cells from children with T cell ALL. 57 Loss of Smad3 protein is a specific feature of pediatric T-cell ALL, but not pre-B-cell ALL. 57 In a mouse model, reduced Smad3 level (Smad3 +/-) and the loss of CDK inhibitor p27 (p27 -/-) synergistically promote T-cell leukemogenesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, since T-ALL represents the rare subtype of paediatric ALL most studies have to be performed in small groups of patients as recently shown. 12 In summary, we investigated in an exploratory study TRF, TA and expression of hTERT in leukaemic cells of paediatric patients with T-ALL and could not observe significant relationships between these biological parameters and clinical outcome or prognosis. Further controlled long-term studies with larger populations are probably needed to elucidate the clinical value of these biochemical markers for monitoring the course of paediatric T-ALL.…”
Section: Telomeres and Telomerase In Paediatric Patients With T-cell mentioning
confidence: 86%